DO R&D EXPENDITURE, MULTINATIONALITY AND CORPORATE GOVERNANCE INFLUENCE TRANSFER PRICING AGGRESSIVENESS? - Mimar Husnaliana Dinca; Vita Elisa Fitriana (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2019)
This research aims to examine the influence of R&D expenditure, multinationality and corporate governance (independent commissioners and shareholders ownership) toward transfer pricing aggressiveness. The prior study recommends determining the factors that affecting transfer pricing aggressiveness in different jurisdictions. Transfer pricing aggressiveness in this research is shown by transfer pricing index, which is the disclosure of transactions with related parties relating to transfer pricing. This research uses 63 multinational companies listed on Indonesia Stock Exchange from 2016-2017. The results indicate regression analysis research and development expenditures have no influence toward transfer pricing aggressiveness. Meanwhile, multinationality has a positive influence on transfer pricing aggressiveness. Moreover, corporate governances represented by independent commissioners and shareholders ownership have negative influences on transfer pricing aggressiveness.